Serpiginous-Like Choroiditis (SLC) – Morphology and Treatment Outcomes. (18th May 2020) - Kawali, Ankush; Bavaharan, Bharathi; Sanjay, Srinivasan; Mohan, Ashwin; Mahendradas, Padmamalini; Shetty, Rohit
ABSTRACT: Purpose: To study morphology and treatment outcomes in serpiginous-like choroiditis (SLC). Methods: A retrospective chart review of SLC cases with ≥1-year follow-up. SLC lesions with elongated borders, thin body named dendritic (D-SLC), large lesions still with elongated borders named advanced dendritic (AD-SLC), and lesions with rounded borders, thick body called placoid (P-SLC). History, investigations, treatment response, and relapses were studied. Results: Thirty-three eyes [D-SLC ( n = 14), AD-SLC ( n = 13), P-SLC ( n = 6)] of 24 patients were studied. Resolution on Fundus autofluorescence achieved at 8.6 months (Range: 4–12 months). 0/16 eyes treated with anti-tubercular therapy (ATT) and 4/11 eyes treated without ATT had at least one recurrence in (D-SLC + AD-SLC) group ( p = .019). Mean best corrected visual acuity at final follow-up was 20/20, 20/25, and 20/60 in D-SLC, AD-SLC, and in P-SLC, respectively. Conclusion: P-SLC has poor visual prognosis compared to AD-SLC and D-SLC. ATT may prevent recurrences in D-SLC and AD-SLC.